Efek Penghambatan Gingerol Terhadap 8- Hidroksideoksiguanosin (8-OHdG) Penginduksi Sel Kanker, HepG2 - Harliansyah, Harliansyah (Majalah Kesehatan Pharmamedika, 2011)
Oxidative stress can damage the function of normal cells and cause pathological conditions. One of the products of oxidative stress is the formation of compounds 8-hydroxy-2'deoksiguanosine (8-OHdG), which is the result of oxidation of the structure of DNA and a risk factor for cancer, atherosclerosis and diabetes on the body's tissues. In this research note that the administration of 1000 ug / ml gingerol reduces the formation of 8-OHdG hepatoma cells (HepG2) is 81.62 Ã‚Â± 5.59 ng / ml versus control significantly (p 0.05; r = 0.76). This result ensures that the antioxidant properties contained in the gingerol can inhibit the activity of free radical markers (8-OHdG) so likely as a preventative against degenerative diseases such as cancer cells.